2015
DOI: 10.1590/1516-4446-2014-1554
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment and staging in bipolar disorder: evidence from clinical practice

Abstract: Objective: Staging models for medical diseases are widely used to guide treatment and prognosis. Bipolar disorder (BD) is a chronic condition and it is among the most disabling disorders in medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Another study assessed pharmacological maintenance treatment across the stages proposed by Kapczinski and colleagues . Authors reported that monotherapy was more frequent in stage I, and two‐drug combinations in stage II, while patients at stages III and IV needed three or more medications or clozapine .…”
Section: Resultsmentioning
confidence: 99%
“…Another study assessed pharmacological maintenance treatment across the stages proposed by Kapczinski and colleagues . Authors reported that monotherapy was more frequent in stage I, and two‐drug combinations in stage II, while patients at stages III and IV needed three or more medications or clozapine .…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation may have been that the approach to assigning stages in model B was not yet validated. Earlier applications of model B by Goi et al and Rosa et al used a semi‐structural interview and the Functional Assessment Short Test to classify subjects according to model B; we used similar items from the QBP . A possible restriction of our study was that for model B the level of functioning was based on a limited amount of self‐rated parameters.…”
Section: Discussionmentioning
confidence: 99%
“…40 The increasing number of medication classes over the stages is in line with earlier studies on treatment resistance. 21,37 Future studies may focus on selecting those variables putting individuals at a higher risk of progressing to more advanced stages, adjusting clinical interventions accordingly.…”
Section: Clinical Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a post hoc analysis from a 15-month randomized controlled trial reported that psychoeducation for caregiver in the prophylaxis of mood episodes appeared beneficial only in patients at early stages [14]. Last, a cross-sectional study reported that monotherapy was more frequent in stage I, and combination of two drugs in stage II, while patients at stages III and IV needed either clozapine or a combination of more than three medications [15].…”
Section: Treatment Refractorinessmentioning
confidence: 99%